A Review of Biomass Resources and Thermochemical Conversion Technologies - Jha, Shivangi; Okolie, Jude A.; Nanda, Sonil; Dalai, Ajay K. (Chemical engineering & technology, 2022)
Waste biomass has the potential to produce renewable fuels and fine chemicals. Biofuels derived from agricultural, forestry, and energy crop systems are promising resources to address climate change and minimize greenhouse gas emissions. The recent advances in various thermochemical technologies for the conversion of waste biomass to value‐added biofuel products are discussed. A summarized outline of thermochemical technologies such as torrefaction, liquefaction, pyrolysis, and gasification is provided. An overview of different types and sources of biomass as well as their physicochemical properties is presented. The thermochemical conversion products and their environmental benefits are considered as well. Agricultural crop residues, energy crops, and woody biomass are potential feedstocks for biofuel production through thermochemical and biological conversion technologies. Bio‐oil, bio‐crude oil, biodiesel, biochar, syngas, biohydrogen, biomethane, bioethanol, and biobutanol are promising biofuel products from waste biomass.